Evaluation the Effects of Different Silica Coating Methods and Silane Types on the Bond Strength Between Polyamide and Polymethylmethacrylate - Atilla Evcin; Özer İşisağ (Current Research in Dental Sciences)
Objectives: The aim of this study is to evaluate the effect of different silica coating methods and silane applications on the bond strength between polyamide and polymethylmethacrylate (PMMA).Methods: Forty-five polyamide specimens were divided into two main groups based on the coating method applied: sol-gel silica coating (S) and tribochemical silica coating (T). Each main group was further divided into two subgroups based on the type of silane used: Bisco Porcelain Primer (BPP) and Clearfil Primer Plus (CPP) (n=9). The control group (C) received no silica coating or silane application. PMMA was then bonded to all specimens, and shear bond strength was evaluated.Results: The highest shear bond strength was observed in group T with BPP application, while the lowest value was recorded in group C. Statistically significant differences were found between S-T and T-C groups (P<.05). Although BPP application in group T resulted in higher bond strength than CPP, the opposite trend was observed in group S.Conclusion: The shear bond strength between polyamide and PMMA can be enhanced by applying silane after silica coating using either the tribochemical or sol-gel method.Keywords: Polyamide, Polymethylmethacrylate, Silica